Public Collaboration in Maine: When and Why It Works - Kenty, Diane; Gosline, Ann; Reitman, Jonathan (Maine Policy Review, 2010)
Government by itself cannot address all complex public policy issues. The authors write that “public collaboration” can alter the discourse on divisive local, regional, and state issues. Public collaboration is a process in which people from multiple sectors (government, business, nonprofit, civic, and tribal) work together to find solutions to problems that no single sector is able to resolve on its own. The authors describe the common features of effective public collaboration and provide detailed case studies and analysis of five recent examples of public collaboration in Maine.
Keywords: Maine; public collaboration; land use planning; ocean energy; watersheds